Debates on Islam and Knowledge in Malaysia and Egypt - Amber Haque (International Institute of Islamic Thought, 2003)
Although the debate on the arrival of the lslamization of knowledge (IOK) concept continues among today's scholars, giving it a practical framework is generally credited to the late Ismail Raji al-Faruqi, a PalestinianAmerican scholar and a founding member of the International Institute of Islamic Thought (HIT). Mona Abaza, associate professor in the School of Humanities and Social Sciences at the American University in Cairo, acknowledges this. She took over 10 years to collect and present her research in this book. The book is divided into three parts with 14 chapters, a hefty 71 pages of notes and bibliography, and a small index. The facts and figures about Malaysia covered in the initial pages are from mid-1998 and therefore, unfortunately, are outdated. In the "introductory reflections," which constitute part 1 of the book, Abaza submits that the topic under discussion is controversial even among Muslim academics. Nevertheless, she has set out to compare the IOK endeavors in two very distinct cultures whose Islamizers, she believes, have a primarily secular training but an Islamic outlook. While Malaysia propagates ...